FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN COMPUTER VISION SYNDROME (CVS) PADA MAHASISWA KEPERAWATAN UNIVERSITAS RIAU - Monaliza Monaliza; Darwin Karim; Siti Rahmalia Hairani Damanik (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Computer Vision Syndrome (CVS) is the syndrome that occur in eyes cause of more interaction with computer. This research aimed to analyze the factors related to CVS in nursing students of Riau University with descriptive correlational design by cross sectional approach. Sampel consisted 209 students were choosen by proportionate stratified random sampling technique. The data was collected by questionnaires and analize by univariate analysis and bivariate analysis using Chi-Square. The characteristic respondent showed that female (92.3%), duration of smartphone usage ≥ 3 hours/ day (93.3%), laptop <4 hours/ day (85.2%), eyes distance to smartphone <30 cm (62.2%), laptop <50 cm (80.3%), not to rest eyes when using smartphone ≥ 10 minutes/ hour (75.1%), laptop (66.7%). The result of research found that there was corellation between the several factors with CVS (p value < α=0,05) that is duration of smartphone usage (p value= 0,015), laptop (p value= 0.042), eyes distance to smartphone (p value= 0,034), laptop (p value= 0.030), rest the eyes when using smartphone (p value= 0.041), and there was no corellation with CVS is rest the eyes when using laptop (p value= 1.000). This research can be information to prevent CVS for laptop and smartphone users. Keywords : Computer Vision Syndrome (CVS), Laptop, Smartphone